An Increase in Learning Outcome Students is Through The Development of Archive E-Module Based on The Flipbook With Discovery Learning Model - Indri Isnaeni; Yuli Agustina (Department of Management, Faculty of Economics, Universitas Negeri Malang, 2018)
The purposes of this research are to produce, to know the validation, and effectiveness of e-module based flipbook with Discovery Learning Model that is produced by researcher. The product resulted from this research and development is e-module based flipbook with Discovery Learning Model in archival with basic competencies Applying Archive Maintenance Procedures.  This research and development uses Lee & Owens consisting of 4 steps: (1) Assessment/Analysis; (2) Design; (3) Development and Implementation; (4) Evaluation. Subjects of this research and development are product technology experts, material experts, and learners. The average product technology expert validation is 95.4 percent, material expert validation is 97 percent, and student validation is 91.6 percent. The e-module is effective to be used in learning activities in the classroom as indicated by the normalized gain test > 0.7 of 0.75.